High-sensitivity cardiac troponin I is a biomarker for occult coronary plaque burden and cardiovascular events in patients with rheumatoid arthritis. (14th March 2018) - Karpouzas, George A; Estis, Joel; Rezaeian, Panteha; Todd, John; Budoff, Matthew J
Abstract: Objectives: Patients with RA display greater occult coronary atherosclerosis burden and experience higher cardiovascular morbidity and mortality compared with controls. We here explored whether pro-inflammatory cytokines and high-sensitivity cardiac troponin I (hs-cTnI), a biomarker of myocardial injury, correlated with plaque burden and cardiovascular events (CVEs) in RA. Methods: We evaluated 150 patients with 64-slice coronary CT angiography. Coronary artery calcium, number of segments with plaque (segment involvement score), stenotic severity and plaque burden were assessed. Lesions were described as non-calcified, mixed or fully calcified. Blood levels of hs-cTnI and pro-inflammatory cytokines were assessed during coronary CT angiography. Subjects were followed over 60 (s .d . 26) months for both ischaemic [cardiac death, non-fatal myocardial infarction (MI), stroke, peripheral arterial ischaemia] and non-ischaemic (new-onset heart failure hospitalization) CVEs. Results: Plasma hs-cTnI correlated with all coronary plaque outcomes ( P < 0.01). Elevated hs-cTnI (⩾1.5 pg/ml) further associated with significant calcification, extensive atherosclerosis, obstructive plaque and any advanced mixed or calcified plaques after adjustments for cardiac risk factors or Framingham D'Agostino scores (all P < 0.05). Eleven patients suffered a CVE (1.54/100 patient-years), eight ischaemic and three non-ischaemic. Elevated hs-cTnI predicted all CVE risk independent of demographics, cardiac risk factors and prednisone use ( P = 0.03). Conversely, low hs-cTnI presaged a lower risk for both extensive atherosclerosis ( P < 0.05) and incident CVEs ( P = 0.037). Conclusion: Plasma hs-cTnI independently associated with occult coronary plaque burden, composition and long-term incident CVEs in patients with RA. Low hs-cTnI forecasted a lower risk for both extensive atherosclerosis as well as CVEs. hs-cTnI may therefore optimize cardiovascular risk stratification in RA.